Dosimetric comparison of two linear accelerators for lung cancer SBRT using IMRT dose delivery technique: VenusX vs. Edge - Yanhua Duan; Shanshan Zhong; Aihui Feng; Qing Kong; Zhiyong Xu (European Journal of Medical Research)
Abstract Background The VenusX and Edge accelerators are two commercially available systems used for lung stereotactic body radiation therapy (SBRT) with Intensity-Modulated Radiation Therapy (IMRT) techniques. Methods A retrospective analysis was conducted on 40 lung cancer patients treated with the Edge accelerator. Treatment plans using both the Edge (PlanEdge) and VenusX (PlanVX) accelerators were generated and evaluated using various dosimetric metrics, employing statistical analyses to identify significant differences. Results For planned target volume (PTV), Plan VX outperformed PlanEdge across the entire cohort, achieving a higher D2 dose (76.84 vs 75.56 Gy, p = 0.005), and showing significant improvements in conformity index (0.84 vs 0.80), homogeneity index (0.50 vs 0.47), and gradient index (5.12 vs 5.62), all with p < 0.001. Plan VX also recorded a lower D2 cm (27.27 vs 27.87 Gy, p = 0.004). Subgroup analyses revealed significant enhancements in conformity index (CI), homogeneity index (HI), and gradient index (GI) for both single and multi-target lesion patients, with multi-target also seeing a notably lower D2 cm. regarding organs at risk (OARs), Plan VX significantly reduced lung mean dose (Dmean) (3.85 to 3.60 Gy), V5 (16.88% to 15.61%), and V20 (5.04% to 4.63%), along with improvements in the great vessels' Dmean and max dose (Dmax), and esophagus’ Dmax across all patients. Single-lesion patients saw consistent lung improvements, while multi-lesion patients experienced significant lung reductions and enhancements in great vessels' and esophagus’ metrics. Conclusions In conclusion, both PlanVX and PlanEdge achieved treatment plans that met the dosimetric criteria defined by the RTOG guidelines. While Plan VX exhibited improved values in CI, HI, and GI, these findings reflect observed dosimetric differences rather than definitive evidence of clinical superiority. Further prospective studies are warranted to evaluate the clinical relevance of these differences.